A broadband polarization-insensitive on-chip reciprocal asymmetric transmission device based on generalized total reflection principle. (27th August 2018) - Fei, Hongming; Wu, Min; Xu, Ting; Lin, Han; Yang, Yibiao; Liu, Xin; Zhang, Mingda; Cao, Binzhao
Abstract: High performance on-chip asymmetric transmission devices are indispensable for all-optical computing and information processing, but has been difficult to achieve. Currently, on-chip asymmetric transmission devices still have some limitations, such as low forward transmittance, narrow working bandwidth and polarization selectivity, which fail to meet the requirements of practical applications. In order to solve above-mentioned problems, we propose to design an on-chip reciprocal asymmetric transmission device based on the generalized total reflection (TR) principle. The on-chip reciprocal asymmetric transmission device consists of two photonic crystals (PCs) with different effective refractive indices. TR of the backward incident light is achieved at the interface by controlling the effective refractive index of the PC structures. This principle eliminates polarization selectivity and increases forward transmittance, contrast and operating bandwidth. The results show that in a broad wavelength region, the PC heterostructure demonstrates asymmetric transmissions for both TE and TM polarization modes with forward transmittance up to 0.58 and 0.78, respectively. And the contrast ratio is higher than 0.9. Our solution provides a new strategy and platform for an on-chip reciprocal asymmetric transmission device that meets the requirements of practical applications.